Suppression of vortex shedding and vortex-induced vibration of a circular cylinder using screen shrouds. (May 2022) - Sun, Chenlin; Azmi, Azlin Mohd; Hao, Zhiyong; Zhu, Hongjun; Zhou, Tongming
Highlights: The screen shrouds can significantly suppress VIV amplitudes, delay the onset of the VIV and narrow the lock-on region. The large-scale vortices are not formed in the near wakes of the screen shrouded cylinders. The strength of the vortical structures in the screen shrouded cylinders are much weaker than that in the bare cylinder. The large-scale vortices in the screen shrouded cylinder wakes are significantly attenuated. Abstract: Experiments were conducted in wind tunnels to investigate the one degree of freedom (1DOF) vortex-induced vibration (VIV) and vortex shedding of a circular cylinder controlled with various screen shrouds in the sub-critical Reynolds number regime. The screen shrouds, made of stainless steel screen meshes with porosities β  = 37%, 48%, 61%, and 67%, were fitted concentrically outside the bare circular cylinder. The diameter ratio between the outer screen shrouds and the inner bare cylinder was fixed at 2. The VIV responses and force coefficients of the screen shrouded cylinders were first examined in a wind tunnel to quantify the effectiveness of the screen shrouds on VIV suppression. It was found that the screen shrouds significantly suppressed the maximum VIV amplitude, delayed the onset of the VIV and narrowed the lock-on region. The maximum VIV amplitude was suppressed by 90% using the β  = 67% screen shroud. To further understand the effect of the shrouds on vortex manipulation, the wake characteristics of the screen shrouded cylinders with β  = 37% and 67% were then examined in a wind tunnel using hot-wire anemometers over a streamwise range x*  = 5−40. Phase-averaging analysis revealed that the large-scale vortices were not formed until x*  = 10 or 20, before which only small-scale vortical structures were identified in the shear layers of the shrouded cylinders, indicating that the screen shrouds successfully delayed the formation of the large-scale vortices. This result was entirely different from the formation of the large-scale structures found in the bare cylinder wake. In addition, the strength of the vortical structures in the former two wakes was much weaker than that in the latter, indicating attenuated large-scale vortices in the screen shrouded cylinder wakes. After the formation of the large-scale structures, the vortices decayed slower in the screen shrouded cylinder wakes than that in the bare cylinder wake.